PENERAPAN FIRST IN FIRST OUT (FIFO) PADA INVENTORY RAW MATERIAL (STUDI KASUS PT. MEKAR ARMADA JAYA) - Sari, Kartika Prasetya; Nevita, Ary Permatadeny; Santoso, Rachmad; Munawi, Hisbulloh Ahlis; Salsabillah, Venus Khatta (Jurnal Inkofar, 2025)
Inventory control is an effort or activity carried out by an agency to make decisions so that the need for materials for production purposes can be met optimally with the smallest possible risk. PT Mekar Armada Jaya (MAJ) is a manufacturing company engaged in stamping and tools. Inventory in this company consists of raw materials, goods in the production process, and goods held for sale. Because inventory is stored in a warehouse, inventory and warehouse management are closely related. Warehousing itself is a component unit in the product supply chain. The warehouse functions as a place to store goods, until they are used in the production process. The purpose of this study is to analyze the application of the FIFO system to raw material inventory at PT MAJ. Data collection techniques used in this study are direct observation in the raw material warehouse, interviews with warehouse staff and the production department, and documentation studies on the inventory recording system. The analysis was carried out qualitatively and quantitatively by comparing conditions before and after the implementation of the FIFO method in several aspects, namely, the level of accuracy of stock recording, the number of expired or damaged raw materials, and the efficiency of raw material retrieval time. The implementation of the FIFO method for inventory control carried out by PT MAJ is by attaching a FIFO label that will experience a color change for each item and change of month, this is done to distinguish new or old inventory. Materials received are given FIFO tags with various colors based on the supplier. The shelves used to store materials are given wheels or plaques, so that when taking materials it is easier. After the goods have been affixed with FIFO labels that are in accordance with the picklist and have been placed in the staging area, a loading list is made to be loaded after which the goods are scanned for their serial numbers by the checker and are ready to be sent. From the results of the analysis, it was concluded that the FIFO method applied at PT. MAJ uses a Kanban system and provides FIFO tags for raw materials, and the control of the system is carried out by people in the PPIC department.Keywords: inventory, FIFO, raw material, label, PPIC